Management Style and Employee Performance in Selected Primary Schools in Kajara County, Ntungamo District - Denis, Kamusiime Banshobeize (Kabale University, 2022)
A Research Report Submitted to the Directorate of Postgraduate Training for the Partial Fulfilment for the Award of Master of Arts in Education Management of Kabale University August